Prediction of the dynamic distribution for Eucheuma denticulatum (Rhodophyta, Solieriaceae) under climate change in the Indo-Pacific Ocean. (September 2022) - Du, Yuqun; Zhang, Jie; Jueterbock, Alexander; Duan, Delin
Abstract: Eucheuma is one of the most important commercial red seaweeds in Southeast Asia, and plays an important role in the global seaweed aquaculture. It is expected to exhibit great responses to ocean warming. Here, we used maximum entropy species distribution models (SDMs) to estimate the suitable habitat of Eucheuma denticulatum under present conditions, and to predict the future range dynamics under the four representative concentration pathway (RCP) scenarios. The best marine environmental factors for E. denticulatum distribution modeling were distance to shore, sea surface temperature and currents velocity. Our results showed that E. denticulatum' distributions would contract in the Central Indo-Pacific Ocean, especially the regions of the Sunda Shelf, while expanding poleward along the south coast of Australia in 2100. Our study provided important knowledge for the prediction of the tropical seaweed distribution, conservation and sustainable developments of E. denticulatum in the future. Highlights: Appliance of maximum entropy to predict the distribution of Eucheuma denticulatum . The influence of climate change on red seaweed's suitable habitats and distribution dynamics. The migration routes of distribution center of tropical seaweed.